Amtsal Kiamat Menurut Penafsiran Al-Zamakhsyari - Sufri Fahmi; Risman Bustamam (Lathaif: Literasi Tafsir, Hadis dan Filologi, 2022)
Al-Zamakshyari interprets the verses of the apocalypse verses using the tahlili method, which is indicated by language analysis indicators or balaghah which are quite focused and detailed when explaining the editorial of certain verses. In terms of the style of interpretation, there is no visible Mu'tazila theological element when Al-Zamakhsyari interprets the verses of the apocalypse. In detail, this study shows that: (a) The interpretation of the doomsday proverbs in Surah Al-Ma'arij verses 8-9 by Al-Zamakhsyari shows the proverbs in the verse to explain the awesomeness of the Day of Judgment, the proverbs in this verse compare the sky with something melting, and comparing the mountains with cotton or feathers blown by the wind, (b) The interpretation of the doomsday proverb in Al-Qari'ah verses 4-5 according to Al-Zamakhsyari shows the proverb in the verse to give an overview of the conditions when the Day of Judgment occurs, the proverb in this verse compares humans with weak animals, and compares the mountains with feathers that are blown by the wind, (c) The interpretation of the doomsday proverb in Al-Qamar verse 7 according to Al-Zamakhsyari shows that the proverb in this verse is a description of the number of people, from the first to the last created, all will be gathered on the day he rises from the grave.